ETHICS OF SOCIAL MEDIA COMMUNICATION ON TIKTOK ACCOUNTS LOADED WITH SARCASM: GEN Z OPINION - Pandjaitan, Rosmawaty Hilderiah; Theresia (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2023)
Gen Z is the largest generation in Indonesia (born 1997-2012) (2020 census results). A generation that enjoys seeking the truth and has access to social media for a long time. They have the most access to TikTok on social media. The issue is that there are many videos on the social media platform TikTok that are sarcastic and contain crude language. What is Gen Z's opinion regarding the communication ethics on social media TikTok that full of sarcasm? In a constructivist paradigm, this kind of qualitative research employs an intrinsic type of case study research methodology. This in-depth interview was conducted with five members of Gen Z from five private university in Jakarta in a semi-structured manner. The outcome: One, according to Gen Z, speaking harshly on social media platform TikTok that is not intended to offend someone is ethical and does not go against the politeness of communication, even though it is full of sarcasm and has a negative impact on society. Depending on the communicator's intention and purpose when communicating; Two, from the perspective of Terminus technikus, knowledge and actions, as well as the capacity to speak roughly, are the results of the learning process; Three, speaking harshly is acceptable as long as it is not intended to be derogatory and is in accordance with manner and custom, which are aspects of human nature; Fourth, dialogic, situational, political, and legal perspectives are employed to elaborate ethical standards on sarcastic accounts. Gen Z does not use religious or ultitarian perspectives; Fifth, speaking harshly can also be used as a way to express courage, optimism, and self- actualization. It can also be used as a way to gain fame and get likes, comments, and followers.